2020
DOI: 10.1155/2020/8866071
|View full text |Cite
|
Sign up to set email alerts
|

Validating a Phenomenological Mathematical Model for Public Health and Safety Interventions Influencing the Evolutionary Stages of Recent Outbreak for Long-Term and Short-Term Domains in Pakistan

Abstract: During the outbreak of an epidemic, it becomes significantly essential to monitor the effects of containment measures and forecast the outbreak, including the epidemic peak. Many countries have either implemented strict lockdown to counter the spread of coronavirus disease or taken necessary preventive measures across the world to reduce the outbreak of this epidemic war. Several epidemic models have been presented across the world to examine the effects of public health-related strategies on mitigating the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…There was no signi cant difference found between males and females for depression and anxiety; however, females had signi cantly higher stress scores compared to males. According to this present data (collected from May to July 2020) it was analyzed that among both genders the females of Karachi city had higher level of depression (83.5%, p -value 0.045) during rst lockdown (from March to August 2020) due to spread of Corona virus among population (15,16) which is similar to the ndings of other studies where 71% severe depression in another city of Pakistan and 85% in Tunisia was found utmost among female gender (17)(18)(19)(20). As it is known that usually females are psychologically more sensitive by the pandemics and the other sudden changes in life (18).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…There was no signi cant difference found between males and females for depression and anxiety; however, females had signi cantly higher stress scores compared to males. According to this present data (collected from May to July 2020) it was analyzed that among both genders the females of Karachi city had higher level of depression (83.5%, p -value 0.045) during rst lockdown (from March to August 2020) due to spread of Corona virus among population (15,16) which is similar to the ndings of other studies where 71% severe depression in another city of Pakistan and 85% in Tunisia was found utmost among female gender (17)(18)(19)(20). As it is known that usually females are psychologically more sensitive by the pandemics and the other sudden changes in life (18).…”
Section: Resultsmentioning
confidence: 80%
“…Whereas con dence limit percentage selected was 5%, Hypothesized % frequency of outcome factor in the population was 50% and with a population sample of 20711000 (15).…”
Section: Data Analysis Planmentioning
confidence: 99%
“…If the value is less than 0.30, this represents that the relationship is somewhat weak between the variables. 0.30 value is considered to be boundary of the weak relationship and considerably strong relationship [39].…”
Section: Research Summary and Concluding Remarksmentioning
confidence: 99%
“…is theory states that the valuable, uncommon, distinguishable, and heterogeneous organizational resources should be arranged and integrated efficiently so they may be deployed to the maximum extent of the quality with better market results. As the management capability approach is an extension to the RBV approach, it examines the business shifts, changes in the market trends, production technology, and changes in Complexity customers' tastes and helps the manufacturing firms to perform functions to react to these shifts [23,24]. e management capability theory brings about alternatives in the organization strategies, policies, resources, technology, and production and marketing methods to meet the evolving requirements [25].…”
Section: Management Capabilitymentioning
confidence: 99%